1999
DOI: 10.1046/j.1469-8137.1999.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced UV‐B radiation under field conditions increases anthocyanin and reduces the risk of photoinhibition but does not affect growth in the carnivorous plant Pinguicula vulgaris

Abstract: The effects of enhanced UV-B radiation were investigated in the carnivorous plant Pinguicula vulgaris in a field experiment performed in Abisko, North Sweden (68m 21h N, 18m 49h E, 380 m above sea level). Potted plants were exposed to either ambient or ambient plus supplemental UV-B radiation, simulating a 15% ozone depletion. No effect was observed on either the epicuticular (external) or cellular (internal) UV absorbing capacity of the leaves. However, the anthocyanin content was more than doubled by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 36 publications
0
37
0
8
Order By: Relevance
“…Sticky exudates from those hairs attract, ensnare, suffocate, and eventually digest small insects. The red pigments, a mix of anthocyanins (Ichiishi et al 1999), clearly did not evolve in this species to repel insects; they may function to attract prey, but a physiological role is just as likely, as has been postulated for anthocyanins in other carnivorous plants (Moran and Moran 1998;Mendez et al 1999). The existence of exceptions does not, of course, vitiate hypotheses for defensive functions of anthocyanins in other red-leafed species.…”
Section: Exceptionsmentioning
confidence: 77%
“…Sticky exudates from those hairs attract, ensnare, suffocate, and eventually digest small insects. The red pigments, a mix of anthocyanins (Ichiishi et al 1999), clearly did not evolve in this species to repel insects; they may function to attract prey, but a physiological role is just as likely, as has been postulated for anthocyanins in other carnivorous plants (Moran and Moran 1998;Mendez et al 1999). The existence of exceptions does not, of course, vitiate hypotheses for defensive functions of anthocyanins in other red-leafed species.…”
Section: Exceptionsmentioning
confidence: 77%
“…The production of anthocyanin in leaves was probably not beneWcial, because anthocyanin had either a negative eVect or no eVect on plant size. This suggests that anthocyanin may be indicative of stress (Lee and Lowry 1980;Mendez et al 1999) or cellular damage (Close and Beadle 2003) in the P. caroliniana complex and may not have a high production cost. However, it is also possible that the production of anthocyanin is reducing some other unknown physiological stress (reviewed in Gould 2004).…”
Section: Leaf Traitsmentioning
confidence: 99%
“…SpeciWcally, we examine the expression and plastic responses of a number of leaf traits including leaf area, shape (width/length ratio), trichome density, reXectance, and anthocyanin content during relatively wet and dry periods of the growth season. We estimated anthocyanin because hybrids vary in widely in their pigmentation (Picotte 2006) and anthocyanins protect the leaf by enhancing photo-chemical quenching of highenergy electrons that may damage cells and reduce the photosynthetic rate (Close et al 2000;Mendez et al 1999). We were particularly interested in the eVects of leaf morphological traits on WUE, measured here with C isotope ratio ( 13 C).…”
Section: Introductionmentioning
confidence: 99%
“…However, exposure to an array of stressors, including UV-B radiation (Mendez et al 1999), osmotic stress (Kaliamoorthy and Rao 1994), drought (Balakumar et al 1993), low temperatures (Krol et al 1995), nutrient deficiencies (Rajendran et al 1992), wounding (Ferreres et al 1997), pathogen infection (Dixon et al 1994), and ozone exposure (Foot et al 1996) have been shown to elicit anthocyanin biosynthesis. This buildup of anthocyanins following stress exposure raises the possibility that anthocyanins may function, in part, to prevent or offset stressinduced damage.…”
Section: Introductionmentioning
confidence: 99%